Response of photomorphogenesis and photosynthetic properties of sweet pepper seedlings exposed to mixed red and blue light - Li, Yan; Xin, Guofeng; Shi, Qinghua; Yang, Fengjuan; Wei, Min (Frontiers in Plant Science, 2023)
Red (R) and blue light (B) have great effects on physiological processes and growth of plants. To investigate how R and BL inﬂuences plant photosynthesis during photomorphogenesis, we examined the growth, plant morphology, photosynthetic response of sweet pepper (Capsicum annuum L.) under RL, BL and different proportions of mixed RL and BL (9R1B, 6R1B, 3R1B, 1R1B, 1R3B), white light as control (CK). The results showed that there were significant differences in growth of pepper seedlings under treatments of different proportions of RL and BL. We made the comparison of monochromatic light and found that the elongation of hypocotyl and first internode as well as leaf expansion were all stimulated by RL, while decreased by BL significantly compared with CK. Conversely, the leaf development, biomass accumulation and photosynthetic properties were inhibited by RL but enhanced by BL. Additionally, compared with CK and other treatments, 3R1B could significantly improve the net photosynthesis rate, gas exchange, photosynthetic electron transport capacity, photochemical efficiency, shoot and root biomass accumulation. Furthermore, seedlings grew robustly and had the highest value of seedling index under this treatment. Overall, these results suggested that pepper seedlings grown under 3R1B performed better, possibly due to the more balanced light spectrum. It was more conducive to improve the plant photomorphogenesis and photosynthesis of sweet pepper, and a higher biomass production and energy utilization efficiency could be achieved simultaneously under this mixed light quality.